Les Obstacles Qui Entravent L’application De L’approche Par Compétences Par Les Enseignants Du Secondaire Qualifiant - Abdelali Arbia; Fatiha Kaddari; Rida Hajji Hour; Abdelrhani Elachqar (European Scientific Journal, ESJ, 2018)
Current educational research is almost unanimous on the fundamental role of the competence approach (CA) for effective learning. In fact, on one hand it promotes a better learning, on the other hand it guarantees less stressful conditions for teachers. To be part of this movement, the Moroccan education system adopted this approach since 2000. Since the implementation of this approach can not succeed without the full support of the faculty, where the questions on the origin of this work: have the teachers adopted this approach, as it actually applied, what are their representations on it. To provide some answers to these questions, we have developed a questionnaire that we sent to the 300 teachers of the Secondary Qualifying cycle of several institutions of the Regional Academy of Education and Training of Fes-Boulemane in Morocco. Analysis of this questionnaire using the SPSS software shows that the main obstacles to the application of CA are four. The first obstacle is the low level of the students, the second obstacle is the overload of the programs the third obstacle is the high number of pupils in the classes and the fourth obstacle is the lack of training of the teachers in the CA. Almost half of teachers report that the objectives of applying the competencybased approach are not being met. Hence the need, to operationalize this approach, to act at all levels namely learners, teachers and curricula.